Common pediatric medical procedures. Nursemaid's elbow - Baum, Rebecca; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2018)
A complete review and demonstration of the reduction maneuver for nursemaid's elbow, with a practical step-by-step visual guide to performing the procedure.
Presenter: Rebecca Baum.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 16, 2020)
Keywords: Elbow -- Wounds and injuries -- Diagnosis; Pediatrics; Documentary films; Instructional films; Nonfiction films; Internet videos; Streaming video; Short films